2017
DOI: 10.1371/journal.pone.0172498
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of long noncoding RNA and messenger RNA signatures in melanoma tumorigenesis and metastasis

Abstract: The incidence of melanoma, the most aggressive and life-threatening form of skin cancer, has significantly risen over recent decades. Therefore, it is essential to identify the mechanisms that underlie melanoma tumorigenesis and metastasis and to explore novel and effective melanoma treatment strategies. Accumulating evidence s uggests that aberrantly expressed long noncoding RNAs (lncRNAs) have vital functions in multiple cancers. However, lncRNA functions in melanoma tumorigenesis and metastasis remain uncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 75 publications
1
27
0
Order By: Relevance
“…Due to nonspecific symptoms, most PC patients are diagnosed with advanced and distant metastasis. Recent study has revealed lncRNAs are essential for tumorigenesis of cancer; [27][28][29][30] nevertheless, the specific mechanisms still remain unclear and require further investigation. 26 Therefore, it is of extreme importance to identify the mechanisms of tumorigenesis and metastasis, thus improving overall survival in PC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to nonspecific symptoms, most PC patients are diagnosed with advanced and distant metastasis. Recent study has revealed lncRNAs are essential for tumorigenesis of cancer; [27][28][29][30] nevertheless, the specific mechanisms still remain unclear and require further investigation. 26 Therefore, it is of extreme importance to identify the mechanisms of tumorigenesis and metastasis, thus improving overall survival in PC patients.…”
Section: Discussionmentioning
confidence: 99%
“…26 Therefore, it is of extreme importance to identify the mechanisms of tumorigenesis and metastasis, thus improving overall survival in PC patients. Recent study has revealed lncRNAs are essential for tumorigenesis of cancer; [27][28][29][30] nevertheless, the specific mechanisms still remain unclear and require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies on molecular mechanisms of melanoma mainly focus on protein‐coding genes, such as NRAS , MTOR , CDKN2A , and BRAF . However, the initiation and progression of melanoma could not be fully explained by protein‐coding genes . High‐throughput transcriptome sequencings have identified tens of thousands of noncoding RNAs, many of which have important roles in biology .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] However, the initiation and progression of melanoma could not be fully explained by protein-coding genes. 9,10 High-throughput transcriptome sequencings have identified tens of thousands of noncoding RNAs, many of which have important roles in biology. 11,12 Long noncoding RNA (lncRNA), which represents a large group of noncoding RNAs, is defined as one with more than 200 nucleotides in length.…”
mentioning
confidence: 99%
“…It has been observed that acquired resistance to BRAF inhibitors is usually characterized by reactivation of the MAPK pathway [16]. There are post-transcriptional adaptive changes which induce the development of drug resistance, these are mostly mechanisms involving non-coding RNAs [17]. In the current mini review we will include the most important molecular pathways and up-to-date treatment modalities in short.…”
Section: Introductionmentioning
confidence: 99%